2021
DOI: 10.1055/s-0041-1731280
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Imaging Vascular Supply of Peripheral Nerves

Abstract: Few studies have been developed to map the vascular structures feeding peripheral nerves, with the majority using cadaveric models and inadequate sample sizes. Preliminary evidence, while limited, indicates that the mapping of these vessels may allow or preclude certain procedures in nerve reconstruction due to the location of essential arterial inflow to the vasa nervorum. This review evaluates the evidence regarding historical, current, and emerging techniques for visualizing these vascular structures in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Recent studies on MRN in patients with T2D have found that structural nerve damage associated with demyelination in T2D is related to elevated levels of hsTNT but not proBNP ( 12 ). While there are several animal experimental MRI studies on the vascular supply of peripheral nerves and monitoring changes in microvasculature ( 13 16 ), only a recent pilot study on dynamic contrast enhanced (DCE) MRN in patients focusing on inflammatory neuropathies could, for the first time, demonstrate that DCE sequences allow investigating the perfusion of peripheral nerves by assessing parameters related to plasma volume and microvascular permeability ( 17 ). These parameters can be obtained from DCE MRN using the extended Tofts model, which allows calculating the constant of the examined nerve’s capillary permeability (K trans ), the volume fraction of the plasma space (v p ), and the volume fraction of the extracapillary extracellular space (v e ) ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on MRN in patients with T2D have found that structural nerve damage associated with demyelination in T2D is related to elevated levels of hsTNT but not proBNP ( 12 ). While there are several animal experimental MRI studies on the vascular supply of peripheral nerves and monitoring changes in microvasculature ( 13 16 ), only a recent pilot study on dynamic contrast enhanced (DCE) MRN in patients focusing on inflammatory neuropathies could, for the first time, demonstrate that DCE sequences allow investigating the perfusion of peripheral nerves by assessing parameters related to plasma volume and microvascular permeability ( 17 ). These parameters can be obtained from DCE MRN using the extended Tofts model, which allows calculating the constant of the examined nerve’s capillary permeability (K trans ), the volume fraction of the plasma space (v p ), and the volume fraction of the extracapillary extracellular space (v e ) ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%